Pedagogical potential of 3D human anatomy software: a new way of teaching and learning in higher education (Research, Society and Development, 2022)
Goal: To analyze the use of two 3D anatomy softwares during the human anatomy course, based on the Cognitive Theory of Multimedia Learning (CTML), proposed by Richard Mayer (2009). Method: This is a descriptive, observational study, with a qualitative approach, by experience report from the reflections experienced during the human anatomy course, from March to June 2022, using two 3D human anatomy softwares "Visible Body 3D Human Anatomy Atlas” and “Introduction to 3D Human Anatomy”. Results: As great potential of the two softwares used in the experiment, we can mention: the virtual manipulation; the availability of anatomical structures in three-dimensional format; greater ease for academics to perceive the shape and location of intended organs; more interesting, attractive, motivating classes and with greater attention and participation of academics. Regarding the CTML principles: coherence, signaling, temporal contiguity and multimedia, both softwares were classified as satisfactory. In relation to redundancy, modality and voice principles, they were classified as unsatisfactory. Conclusion: The effect of reducing the amount of information, allowed by the software’s features, allowed to avoid cognitive overload, having positive consequences at the level of teaching in the subject. However, it is necessary that the teacher, when using these types of softwares for classes, pay attention and caution in the selection, using theoretical-methodological parameters, such as CTML, in order to diagnose the elements that may interfere with the learning of the topic addressed, aiming at better conditions for the development of academics' learning in the discipline of human anatomy.